An Automatic Assembly SMT Production Line Operation Technological Process Simulation Model Development - Yevsieiev, V.; Maksymova, S.; Starodubcev, N. (International Science Journal of Engineering & Agriculture, 2023)
This article describes an automatic assembly SMT production line operation technological process simulation model development within the framework of modern cyber-physical production systems. In the course of the research, the authors conduct an analysis of modern publications on the topic of research, and the need to find new approaches for modeling the work of a production line at the initial stages of design. This makes it possible to assess the load on each element of the system at the design stage, and identify disadvantages at the early stages of production planning. The authors give an example of the task solution for modeling a fragment of an automated production line of SMT assembly, based on the use of typical mathematical schemes of mass service systems (MSS). A description of the functioning of the technological link of the process is carried out, and a Q-diagram of the technological process of SMT assembly is developed. Using the simulation modeling language GPSS and the technological parameters of the selected equipment, a block diagram was developed, on the basis of which the program was written and the work of the SMT assembly production line was simulated. The obtained results further allow us to estimate the production capacity, the loading of each equipment, the functioning processes of both the selected fragment, and the developed model and they can be applied to the simulation of large production lines within the framework of PCB production.
Keywords: Industry 4.0, Cyber-Physical System, PCB, Automated Production Line, SMT, GPSS.